2007
DOI: 10.1038/sj.cdd.4402230
|View full text |Cite
|
Sign up to set email alerts
|

The homeobox gene Arx is a novel positive regulator of embryonic myogenesis

Abstract: Skeletal muscle fibers form in overlapping, but distinct phases that depend on the generation of temporally different lineages of myogenic cells. During primary myogenesis (E10.5-E12.5 in the mouse), embryonic myoblasts fuse homotypically to generate primary fibers, whereas during later development (E14.5-E17.5), fetal myoblasts differentiate into secondary fibers. How these myogenic waves are regulated remains largely unknown. Studies have been hampered by the lack of markers which would distinguish embryonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 40 publications
1
29
0
Order By: Relevance
“…Aristaless-like proteins are thought to act as either transcriptional activators or transcriptional repressors (29,30,(33)(34)(35)(36)(37). In C. elegans, Melkman and Sengupta (20) found that alr-1 blocked expression of the DD motor neuron marker flp-13 in VD motor neurons and both down-regulated and up-regulated lin-11 expression in the AWA and ASG neurons, respectively.…”
Section: Alr-1 Functions In Trn Differentiation As a Transcriptional mentioning
confidence: 99%
“…Aristaless-like proteins are thought to act as either transcriptional activators or transcriptional repressors (29,30,(33)(34)(35)(36)(37). In C. elegans, Melkman and Sengupta (20) found that alr-1 blocked expression of the DD motor neuron marker flp-13 in VD motor neurons and both down-regulated and up-regulated lin-11 expression in the AWA and ASG neurons, respectively.…”
Section: Alr-1 Functions In Trn Differentiation As a Transcriptional mentioning
confidence: 99%
“…6G-I), these secondary fibers do not form in nfixa-MO-injected embryos at 3 dpf, whereas they are present in rescued embryos. Moreover, we injected embryos with nfixa-MO and treated them with cyclopamine, which inhibits Hh signaling and blocks primary slow fiber formation (Biressi et al, 2008;Chen et al, 2002). Cyclopamine-treated control embryos normally developed secondary slow muscle fibers at the dorsal and ventral extremes of the myotome, whereas in nfixa-MO-injected embryos the secondary fibers were not formed.…”
Section: Research Articlementioning
confidence: 99%
“…Subsequently, ARX orthologs were detected in the forebrain of chickens (Cobos et al 2005), Xenopus (El-Hodiri et al 2003, Kelly et al 2005, Seufert et al 2005, and Caenorhabditis elegans (Melkman & Sengupta 2005). The ARX protein contains a Q (50) paired-type homeodomain, a C-terminal aristaless domain, and an N-terminal octapeptide and acts as a nuclear transcriptional regulator to activate or inhibit gene expression (Seufert et al 2005, McKenzie et al 2007, Biressi et al 2008, Fullenkamp & El-Hodiri 2008, Colasante et al 2009). The ARX gene encodes a 562-amino acid protein (Ohira et al 2002, Stromme et al 2002 with four characteristic polyalanine (PolyA) tracts where most of the ARX mutations occur (Gecz et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Deficiency of Arx results in a loss of mature endocrine a-cells with a concomitant increase in the numbers of b-and d-cells (Collombat et al 2003), suggesting that Arx is required for the specification and differentiation of a-cells (Collombat et al 2003. Arx is strongly expressed in differentiating embryonic muscle and is progressively decreased during myogenesis, acting as a positive regulator of the differentiation and specification of skeletal muscle fibers (Biressi et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation